2000
DOI: 10.1007/pl00009991
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial community structure and colonization patterns of Fagus sylvatica L. ectomycorrhizospheres as determined by fluorescence in situ hybridization and confocal laser scanning microscopy

Abstract: The bacterial community structure of ectomycorrhizospheres on beech (Fagus sylvatica) grown in natural forest soil in southern Germany was examined by fluorescence in situ hybridization (FISH) using fluorescent oligonucleotide probes, targeting phylogenetic relevant sequences of the 16S and 23S rRNA. Lactarius subdulcis, L. vellereus, L. rubrocinctus and Laccaria amethystina were found to be the prevalent fungi forming ectomycorrhizae with F. sylvatica. For FISH studies using confocal laser scanning microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
58
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 38 publications
5
58
0
1
Order By: Relevance
“…In general, few data for uncultured bacteria in fungi have been presented (11,12,50), and only recently have a few phylogenetic studies identified an endophytic bacterium that is the endosymbiont of G. margarita and is a member of the genus Burkholderia (7) and members of the alpha and beta subclasses of the Proteobacteria detected in ectomycorrhizae of F. sylvatica, L. vellereus, and L. subdulcis (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, few data for uncultured bacteria in fungi have been presented (11,12,50), and only recently have a few phylogenetic studies identified an endophytic bacterium that is the endosymbiont of G. margarita and is a member of the genus Burkholderia (7) and members of the alpha and beta subclasses of the Proteobacteria detected in ectomycorrhizae of F. sylvatica, L. vellereus, and L. subdulcis (33).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason in this study we attempted to use a combination of morphological and molecular 16S rRNAbased approaches to survey the presence of potential bacterial endo-and epiphytes associated with the ectomycorrhizal fungus Tuber borchii Vittad. These tools have been used previously to identify endophytic bacteria such as the Burkholderia endosymbiont of Gigaspora margarita (7) and members of the alpha and beta subclasses of the Proteobacteria detected as epibionts in ectomycorrhizae of Fagus sylvatica, Lactarius vellereus, and Lactarius subdulcis (33).…”
mentioning
confidence: 99%
“…Since nonphotosynthetic endobacteria are completely enclosed within the fungal hypha, they must also obtain their nutrients solely from the fungal cytoplasm. Little is known of the trophic exchanges that occur during these interactions; however, while fungal endobacteria have been observed in dead hyphae (37,255), they are generally not considered to cause hyphal damage like other mycophagous bacteria. The flow of nutrients in a BFI may not always be directed to the bacterial partner (Fig.…”
Section: Bacterial-fungal Molecular Interactions and Communicationmentioning
confidence: 99%
“…The same holds true for the mycorrhizal mantle (13,14). Besides other functions, these prokaryotes are able to catalyze the mineralization of organic matter.…”
mentioning
confidence: 75%
“…This treatment corresponds to a daily amount of 0.337 mg 15 N in excess of the natural abundance. Eight trees from each site that were not labeled with 13 C and 15 N were maintained as nonlabeled controls in another greenhouse.…”
Section: Methodsmentioning
confidence: 99%